Weed control in establishing mixed swards of clover plantain and chicory - Gawn, T.L.; Harrington, K.C.; Matthew, C. (New Zealand Plant Protection, 2012)
A field trial was conducted in Palmerston North to assess weed control options for establishing mixed swards of chicory (Cichorium intybus) narrowleaved plantain (Plantago lanceolata) red clover (Trifolium pratense) and white clover (Trifolium repens) a pasture mixture currently popular for finishing lambs Haloxyfop safely controlled grass weeds and mowing twice during the first few months of establishment helped control some broadleaved weeds Flumetsulam was the safest herbicide for controlling broadleaved weeds although it caused severe suppression of plantain initially All other treatments caused unacceptable levels of damage to at least one of the sown species If chicory was not included in the mix then bentazone paraquat/diquat and diuron could be used Options for an integrated weed control programme for the mixture of four species are discussed For young cloverbased pastures hemlock (Conium maculatum) will be controlled better by flumetsulam or bentazone than 24DB